Dynamics of the Stool Virome in Very Early-Onset Inflammatory Bowel Disease. (14th May 2020) - Liang, Guanxiang; Conrad, Maire A; Kelsen, Judith R; Kessler, Lyanna R; Breton, Jessica; Albenberg, Lindsey G; Marakos, Sarah; Galgano, Alissa; Devas, Nina; Erlichman, Jessi; Zhang, Huanjia; Mattei, Lisa; et al.
Abstract: Background and Aims: Dysbiosis of the gut microbiota is a well-known correlate of the pathogenesis of inflammatory bowel disease [IBD]. However, few studies have examined the microbiome in very early-onset [VEO] IBD, which is defined as onset of IBD before 6 years of age. Here we focus on the viral portion of the microbiome—the virome—to assess possible viral associations with disease processes, reasoning that any viruses potentially associated with IBD might grow more robustly in younger subjects, and so be more detectable. Methods: Virus-like particles [VLPs] were purified from stool samples collected from patients with VEO-IBD [ n = 54] and healthy controls [ n = 23], and characterized by DNA and RNA sequencing and VLP particle counts. Results: The total number of VLPs was not significantly different between VEO-IBD and healthy controls. For bacterial viruses, the VEO-IBD subjects were found to have a higher ratio of Caudovirales vs to Microviridae compared to healthy controls. An increase in Caudovirales was also associated with immunosuppressive therapy. For viruses infecting human cells, Anelloviridae showed higher prevalence in VEO-IBD compared to healthy controls. Within the VEO-IBD group, higher levels of Anelloviridae DNA were also positively associated with immunosuppressive treatment. To search for new viruses, short sequences enriched in VEO-IBD samples were identified, and some could be validated in an independent cohort, although none was clearly viral; this provides sequence tags to interrogate in future studies. Conclusions: These data thus document perturbations to normal viral populations associated with VEO-IBD, and provide a biomarker— Anelloviridae DNA levels—potentially useful for reporting the effectiveness of immunosuppression.